Should indigenous knowledge in development be redefined? Lessons from the artisanal mining sector in Ghana - Ofori, Alesia D.; Mdee, Anna L. (Liverpool University Press, 2025)
Indigenous knowledge is often posed as a unified body of knowledge, undefiled and somewhat sanctimonious. When it does not appear so, it is claimed that indigenous knowledge, particularly, has been ‘adulterated’ by Westernised ideologies from colonialism and modernisation. This perceived dichotomy, i.e. indigenous versus modern knowledge, often ignores the possibility of hybridised knowledge, a continuous and complicated everyday process whereby various forms of knowledge blend in space and time. This paper, therefore, argues that the existence of dichotomous and distinct forms of knowledge is a mirage. Rather, what may be termed indigenous is a co-produced knowledge by multiple actors and agents, having evolved through rigorous negotiations, legitimisation and politico-economic contestations. We make this point by analysing the bricolage processes of alteration and aggregation between ideologies perceived to be rooted in African indigenous knowledge systems, and modern, colonially rooted religious ideologies in a Ghanaian mining village. The paper highlights the importance of context in these discussions. We conclude that particularly in rapidly shifting socio-economic, political and cultural landscapes, indigenous knowledge as a distinct body of applicable knowledge remains contestable and complex and therefore solicits for intentional dissection and detangling, especially within development practice.
Keywords: 4404 Development Studies; 44 Human Society; Urban & Regional Planning; 4407 Policy and administration